Preliminary experiences with limbal relaxing incision for treatment of astigmatism during phacoemulsification - Sharma, BR; Kumar, A (Nepalese Journal of Ophthalmology, 2010)
Introduction: This small study relates our early experiences with the Limbal Relaxing Incision (LRI) for management of astigmatism in patients undergoing cataract surgery. Aims: To evaluate the efficacy of LRI in the management of primary astigmatism when combined with phacoemulsification. Subjects and methods: Limbal relaxing incisions were performed to correct primary astigmatism in 12 eyes of 12 cataract patients who underwent phacoemulsification as the primary procedure. The length and number of incisions were determined using the AMO LRI calculator software programme using Donnenfield and NAPA nomograms. Keratometric astigmatism was measured preoperatively and postoperatively on day 1 and after 3 weeks or more. Surgically-induced astigmatism (SIA) and the intended angle of error were evaluated by the vector analysis method. Preoperative and postoperative uncorrected visual acuity (UCVA) and best spectacle corrected visual acuity (BSCVA) were evaluated in each visit. Results: The mean age of patients was 52.92 ±10.91 years. There were 75 % male and 25 % female patients. The mean keratometric preoperative astigmatism was 2.08 ±1.05 diopter. The mean 1st postoperative day keratometric astigmatism was 1.74 ±1.32 diopter and the mean final keratometric astigmatism at 3 weeks postoperatively was 1.05± 0.68 diopter. The mean SIA on the 1st postoperative day was 2.97 ±1.72 diopter at 103.25±56.57 degree with intended angle of error 6.53±9.61 degree. The mean SIA on the 3rd postoperative week was 2.26±0.87 Diopter at 107.08±49.96 degrees with intended angle of error 2.90±7.87 degrees. Conclusion: Limbal relaxing incisions are effective method to reduce postoperative astigmatism with good predictability of intended angle. Keywords: limbal relaxing incision (LRI); uncorrected visual acuity (UCVA); surgically induced astigmatism (SIA); angle of error; target astigmatic treatment (TAT) DOI: 10.3126/nepjoph.v1i2.3681 Nep J Oph 2009;1(2):90-94